2020
DOI: 10.1037/pha0000322
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral economic demand for medications and its relation to clinical measures in multiple sclerosis.

Abstract: Multiple sclerosis (MS) is a neurodegenerative disorder that causes a wide range of symptoms, which, if left untreated, worsen over time. Despite the availability of effective medications, however, many MS patients fail to take their medications. One possibility is that these patients fail to follow through on treatment recommendations because they do not value these treatments-despite their effectiveness. Prior studies have used principles of microeconomic demand to quantify subjects' valuation of commodities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…During the medical decision‐making task (Jarmolowicz, Reed, Bruce, et al, 2018; Jarmolowicz et al, 2020), patients indicated their likelihood of taking a hypothetical DMT on an 11‐point decile scale (i.e., 0, 10, 20, 30, 40, 50, 60, 70, 80, 90, and 100%). On the opening screen of the task, patients were told that they were making decisions about a hypothetical DMT that has mild side effects (adapted from the World Health Organizations adverse effects reporting guidelines; World Health Organization, 2005):
Mild side effects are intermittent and cause mild discomfort.
…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…During the medical decision‐making task (Jarmolowicz, Reed, Bruce, et al, 2018; Jarmolowicz et al, 2020), patients indicated their likelihood of taking a hypothetical DMT on an 11‐point decile scale (i.e., 0, 10, 20, 30, 40, 50, 60, 70, 80, 90, and 100%). On the opening screen of the task, patients were told that they were making decisions about a hypothetical DMT that has mild side effects (adapted from the World Health Organizations adverse effects reporting guidelines; World Health Organization, 2005):
Mild side effects are intermittent and cause mild discomfort.
…”
Section: Methodsmentioning
confidence: 99%
“…Patients completed a medication purchase task based on prior studies on MS patients (Jarmolowicz et al, 2020). Patients were asked to report their likelihood of purchasing a year's supply of effective medication across a range of prices (20 values ranging from free to $500,000/year).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Demand is often analyzed in a demand curve, which displays the functional relation between the amount of a commodity/activity consumed and its price. Demand analysis has been used to quantify the likelihood of initiating and continuing other health‐related behaviors, such as treatment selection (Gilroy & Feck, 2022; Gilroy et al, 2022), drug use (e.g., Jacobs & Bickel, 1999; MacKillop et al, 2008; Murphy & MacKillop, 2006), food intake (e.g., Epstein et al, 2010, 2018), problematic technology use (e.g., Hayashi & Blessington, 2021; Hayashi et al, 2019a, 2019b), risky sex (e.g., Dolan et al, 2020; Harsin et al, 2021; Jarmolowicz et al, 2016; Strickland et al, 2020), medication adherence (e.g., Jarmolowicz et al, 2019, 2020), and exercising (e.g., Anokye et al, 2012). In a typical demand task, consumption is quantified by the amount of a commodity/activity consumed at a given price, but it can also be quantified by the probability of a commodity/activity consumed (Roma et al, 2016, 2017).…”
Section: Breastfeeding and Behavioral Economic Demand Analysismentioning
confidence: 99%